Traits of shattering resistant buckwheat 'W/SK86GF' - Suzuki, Tatsuro (Breeding science, 2012)
Seed shattering is a significant problem with buckwheat, especially at harvesting time. Several reports have shown that a green-flower mutant of buckwheat, such as W/SK86GF, has a strong pedicel. Although a strong pedicel may provide some resistance to shattering in the field, no study has thoroughly examined this issue. In this paper, we demonstrate that a W/SK86GF has shattering resistance by comparing the degrees of shattering of W/SK86GF and Kitawasesoba (leading variety of Hokkaido with non-green-flower traits) through a test for four years, including a typhoon hit year in the field. In a non-typhoon year, the shattering seed ratio (shattering seed weight/(yield + shattering seed weight) × 100) of W/SK86GF at maturing time +15 days (+15D) was lower than that of Kitawasesoba. In a typhoon hit year, the shattering seed ratios of Kitawasesoba at maturing time and +15D were surprisingly high, 14.4 and 21.1%, respectively. On the other hand, those of W/SK86GF were only 3.08% and 2.57%, respectively; indicating W/SK86GF is promising as a shattering resistant line even in a typhoon hit year. From these results, shattering resistance of W/SK86GF can be evaluated after maturing time such as +15D and pedicel strength would confer W/SK86GF a shattering resistant trait